Deletion of maize RDM4 suggests a role in endosperm maturation as well as vegetative and stress-responsive growth. (16th July 2020) - Jia, Shangang; Yobi, Abou; Naldrett, Michael J; Alvarez, Sophie; Angelovici, Ruthie; Zhang, Chi; Holding, David R
Abstract: Opaque kernels in maize may result from mutations in many genes, such as OPAQUE-2 . In this study, a maize null mutant of RNA-DIRECTED DNA METHYLATION 4 ( RDM4 ) showed an opaque kernel phenotype, as well as plant developmental delay, male sterility, and altered response to cold stress. We found that in opaque kernels, all zein proteins were reduced and amino acid content was changed, including increased lysine. Transcriptomic and proteomic analysis confirmed the zein reduction and proteomic rebalancing of non-zein proteins, which was quantitatively and qualitatively different from opaque-2 . Global transcriptional changes were found in endosperm and leaf, including many transcription factors and tissue-specific expressed genes. Furthermore, of the more than 8000 significantly differentially expressed genes in wild type in response to cold, a significant proportion (25.9% in moderate cold stress and 40.8% in near freezing stress) were not differentially expressed in response to cold in rdm4, suggesting RDM4 may participate in regulation of abiotic stress tolerance. This initial characterization of maize RDM4 provides a basis for further investigating its function in endosperm and leaf, and as a regulator of normal and stress-responsive development. Abstract : Loss of RDM4 in maize causes global zein reduction, opaque endosperm, and extensive proteome rebalancing, as well as plant developmental delay, male sterility, and massively altered transcriptional response to cold.